PRAKTIK PELEPAS UANG/RENTENIR di Nagari Lubuk Basung Kabupaten Agam Sumatera Barat - Frans Efendi Panjaitan; Nofrion . (JURUSAN GEOGRAFI FIS UNP, 2018)
ABSTRACT This research discuss about money lending in Nagari Lubuk Basung Agam Regency West Sumatera. This research aims to get informations, to analyze, and to conclude the data about money lenders profile, working procedure of the money lenders, costumers profile of the money lenders, money lending factors, and impact of money lending. Type this research is qualitative descriptive, the informan are money lenders and costumer. Data collecting technique are observation, interview, and documentation, which is analyzed with reduction, interpretation, and conclution. Research finding result are: (1) Money lenders and costumers are from various background such as culture, religion, education, occupation, income, etc. (2) The loan interest is 20 % in 40 days. (3) The dependence relationship between money lenders and costumers. Key words: money lenders,costumers